أهمية التنمية المهنية المستدامة ودورها في تطوير العمل المدرسي في ضوء معايير الجودة الشاملة - الصالحية، فاطمة بنت محمد بن سالم (كلية التربية جامعة 6 أكتوبر بالتعاون مع رابطة التربويين العرب, 2017)
تهدف الورقة الحالية إلى تسليط الضوء على أهمية التنمية المهنية المستدامة في تطوير العمل المدرسي في ضوء معايير الجودة الشاملة، والتوصل إلى إجراءات مقترحة لتفعيل برامج التنمية المهنية المستدامة. حيث أنه وفي ظل الاستراتيجيات التربوية الحديثة والتحديات التي تواجه المدرسة كمؤسسة تربوية مجتمعية، والتي جاءت نتيجة للتحولات والتغيرات المتسارعة، جاءت الحاجة إلى المبادرات في تطوير وظيفة المدرسة كمؤسسة تربوية اجتماعية وتطوير طبيعة أدوار العاملين فيها وأدواتها ووسائطها وأساليبها. وتلعب التنمية المهنية المستدامة في هذا الجانب دورا مهما وحيويا، وذلك لأنها فلسفة تقوم على التفكير بطريقة شمولية تكاملية من خلال استخدام أسلوب النظم الكلية والفرعية، وما يربطها من علاقات وتفاعلات وما يترتب عليها من نتائج وعمليات وتغذيه راجعة في التعامل مع المشكلات. وتعد الجودة الشاملة أحد المداخل الإدارية المعاصرة التي تلعب دورا حيويا ومتميزا في مساعدة المؤسسات والأفراد، من خلال منهجية فكرية وعملية متكاملة الأدوات والوسائل والمعايير والتقنيات، يسودها ثقافة التميز رغبة في إرضاء العاملين والمتعلمين، كما أن غالبية المؤسسات التربوية أصبحت تؤكد على جودة التدريب من خلال وضع خططا وبرامج للتنمية المهنية المستدامة في ضوء نتائج التقويم الذاتي للمؤسسة والعاملين فيها، ودعم تلك البرامج فنيا ومعنويا وماديا التي يستطيع العاملون من خلالها التعامل بكفاءة مع مصادر المعرفة المتنوعة سعيا وراء إيجاد بيئة مهنية وتنظيمية مشجعة للتطور والتحسين. The presented paper aims to highlight the importance of sustainable profession development in the improvement of school work while optimizing overall quality standards. Modern educational strategies and the challenges facing schools as a communal educational institution, came as a result of shifts and rapid changes. These challenges assure the need for initiatives in the development and improvement of function of schools as social educational institutions, and the development of the roles of this educational institute, and promote effective tools and methods to tackle fluctuating challenges faced. Sustainable profession development in this aspect plays an important and vital role, since it is a belief based on thinking in an all-inclusive way as well as targeting specific details affecting the overall system. The consequent feedback and results therefore play and overall aspect in the optimization of solutions for the challenges faced. The overall comprehensive quality is one of the modern administrative approaches that play a vital role in helping organizations and individual employees through a distinctive and practical methodology that includes tools, methods, standards and techniques. There is a culture of excellence and the desire to gratify workers and learners in such fields. The majority of the educational institutions have engaged in quality control through the development of their strategies and programs for sustainable profession development, through self-evaluation by the institution and its employees. Support of these programs is vital technically and financially through which employees can deal efficiently with the sources of diverse knowledge in order to create an encouraging professional and regulatory environment for development and improvement.
Keywords: إعداد المعلمين -- العمل المدرسي -- التنمية المهنية -- التنمية المستدامة -- الجودة الشاملة